(( The level of job performance of the employees of the Faculty of Humanities at Asmarya University and its relationship to their personal background )) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:Proceeding from the importance of performance and its level of quality in the advancement of work, the improvement and development of achievement, and the optimal use of time, this research presents a field study conducted by the researcher during the year 2022 AD, in the College of Human Sciences at Al Asmarya University in Libya, in which the researcher evaluated the level of job performance among the college staff , By analyzing the data of the study tool (questionnaire), as well as knowing the relationship between the results of the level of performance, and the variables of the personal background of the respondents.